Hd1 Allele Types and Their Associations with Major Agronomic Traits in Korean Rice Cultivars - Youngjun Mo; Chang-Min Lee; Hyang-Mi Park; Su-Kyung Ha; Mi-Jung Kim; Jieun Kwak; Hyun-Sook Lee; Jeong-Heui Lee; Ji-Ung Jeung (Plants, 2021)
Optimizing flowering time in crop plants is critical for maximizing yield and quality under target environments. While there is a wide range of heading date variation in Korean rice cultivars, the underlying gene mechanisms are unclear. Here, we sequenced the protein coding regions of Hd1, the major rice heading date gene, from 293 Korean rice cultivars and investigated the associations between Hd1 allele types and major agronomic traits under four different environments. There were four functional Hd1 and five nonfunctional hd1 alleles distributed among the 293 Korean rice cultivars. The effects of the Hd1 allele types were highly significant for days to heading in all four environments, explaining 51.4–65.8% of the phenotypic variation. On average, cultivars carrying nonfunctional hd1 headed 13.7 days earlier than those carrying functional Hd1. While the Hd1 allele types exhibited highly significant effects on culm length and protein content under all four environments, the differences between cultivars carrying Hd1 and hd1 were minimal. The effects of the Hd1 allele types on amylose content were significant in only one of the four environments. Our results provide useful information for fine-tuning rice heading dates by utilizing different Hd1 alleles in rice breeding programs.